Chapter A proposito dell'autore del Choždenie na Florentijskij sobor - Skomorochova, Lilia (Biblioteca di Studi Slavistici, 2019)
The anonymous Choždenie na Florentijskij sobor is one of four works written by Russian envoys to the Council of Ferrara-Florence (1438-1439), an event that sealed the union of the Catholic and Orthodox Churches. This article addresses the problem of that unknown author's social status, an issue of controversy in the several studies devoted to this text beginning in the 19th century. Our linguistic and stylistic analysis examines the author in terms of his cultural literacy and explores how his conception of literary standards was shaped by specific experiences of reading and writing.